Treatment of HCV infection in Poland at the beginning of the interferon‐free era—the EpiTer‐2 study. Issue 6 (6th February 2018) - Flisiak, R.; Zarębska‐Michaluk, D.; Janczewska, E.; Staniaszek, A.; Gietka, A.; Mazur, W.; Tudrujek, M.; Tomasiewicz, K.; Belica‐Wdowik, T.; Baka‐Ćwierz, B.; Dybowska, D.; Halota, W.; et al.
Summary: The aim of the EpiTer‐2 study was to analyse patient characteristics and their medication for HCV infection in Poland at the beginning of the interferon‐free era. Analysis of data of HCV infected patients treated during the initial period of availability of interferon‐free regimens in Poland, who started therapy after 1 July 2015 and had available an efficacy evaluation report before 30 June 2017 was undertaken. A total of 2879 patients with chronic hepatitis C were entered, including 46% with liver cirrhosis. The most common was genotype 1b (86.8%). The study population was gender balanced, the majority of patients were overweight or obese and 69% presented comorbidities, with the highest prevalence that for hypertension. More than half of patients were retreated due to failure of previous therapy with pegylated interferon and ribavirin. Almost two‐third of patients received current therapy with ombitasvir/paritaprevir/ritonavir±dasabuvir (OPrD) ±ribavirin. Other patients received mostly sofosbuvir‐based regimens including combination with ledipasvir and pegylated interferon and ribavirin for genotype 3‐infected patients. Efficacy of treatment in the whole study population measured as intent‐to‐treat analysis was 95%. The most frequent regimen, administered for patients infected with genotype 1b, was 12 weeks of OPrD, resulting in an SVR rate of 98%. At least one adverse event was reported in 38% of patients, and the death rate was 0.8%.In conclusion, data from the EpiTer‐2 study confirmed the excellent efficacy and safety profile of the real‐world experience with recently introduced therapeutic options for genotype 1 HCV infection, but demonstrated weakness of the current therapeutic programme regarding genotype 3 infections.